THE MODERN INVENTION OF "SCIENCE‐AND‐RELIGION": WHAT FOLLOWS?: with Peter C. Kjærgaard, "Why We Should Care about Evolution and Natural History"; Kaspar von Greyerz, "Early Modern Protestant Virtuosos and Scientists: Some Comments"; Nathan J. Ristuccia, "Peter Harrison, Ludwig Wittgenstein, and the Problem of Pre‐Modern Religion"; Michael Fuller, "Into Terra Incognita: Charting beyond Peter Harrison's The Territories of Science and Religion"; and Peter Harrison, "The Modern Invention of 'Science‐and‐ Religion': What Follows?". Issue 3 (September 2016) - Harrison, Peter
Abstract: I am grateful to the four reviewers of The Territories of Science and Religion for their careful and insightful readings of the book, and their kind words about it. They all got the central arguments pretty much right, and thus any critical comments are not the result of fundamental misunderstandings. While there are some common themes in the assessments, each reviewer, happily, has offered a distinct perspective on the book. For this reason I will deal with their comments in turn, but with a focus throughout on a generally expressed concern about the broader implications of the book's historical analysis, and what positive or concrete proposals might follow from it.